Peningkatan Kinerja Karyawan Hotel Berbasis Talent Management - Mozes Tomasila; Godprit Haris Touwely (Univiversitas Dr. Djar Wattiheluw, 2022)
One of the strategies that can be used in creating qualified human resources in terms of performance, ethics, or abilities and skills is the application of Talent Management. In this context, companies can run training on Talent training. This research is intended to conduct a study on